Corporate Governance : nowe trendy w europejskim prawie spółek - Czyczerski, Marcin (Corporate governance : new trends in the European company law, 2006)
The article describes the role of Corporate Governance in the contex of new trends in the European company law. Corporate Governance is nowadays the way in which companies are directed and controlled. Its rules are crucial for determining the overall attractiveness and prosperity of capital markets and companies. It is attracting an increasing attention on both sides of the Atlantic Ocean. The interest derive from painful past experience. Corporate Governance framework is found as a key condition for properly functioning companies and capital markets. European regulations are going to set up a framework, which then enables the markets to play their disciplining role in an efficient way. American regulations try to set up a law provisions mostly by a commonly known as Sarbanes Oxely Act. The other important issue in respect of corporate governance rules is reorientation of the goals and acting of the Supervisory Board. An effective Audit Committee as the active part of Supervisory Board should play a significant role in implementing corporate governance rules.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 73-79